Preparation method of ultrafine boehmite
Patent Information
- Application Number
- CN202611061241.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-08-18
AI Technical Summary
然而,当前公开的各类制备路线在实际放大和产品质量控制方面仍面临较明显的制约
本申请实施例提供了一种超细勃姆石的制备方法,所述方法包括:将硫酸铝溶液与铝酸钠溶液进行中和反应,得到活性氧化铝水合物晶种浆料;其中,所述活性氧化铝水合物晶种浆料的固含量以氧化铝质量计为2%~6%,所述中和反应的终点pH值为7~10;将所述活性氧化铝水合物晶种浆料加入到氧化铝浓度为90g/L~110g/L的铝酸钠溶液中,以进行种分反应,得到分解料浆;其中,所述活性氧化铝水合物晶种浆料中所含氧化铝的质量占所述铝酸钠溶液中氧化铝总质量的10%~40%,所述种分反应的温度为30℃~65℃;将所述分解料浆进行固液分离,得到滤饼;对所述滤饼进行洗涤,得到超细氢氧化铝前驱体;将所述超细氢氧化铝前驱体与水进行混合打浆,得到固含量为10%~30%的前驱体浆料;将所述前驱体浆料在170℃~220℃下水热压煮1小时~4小时,得到超细勃姆石粉体。在硫酸铝溶液与铝酸钠溶液的中和反应中,通过控制反应产物的固含量以及中和反应的终点pH值,原位生成具有高比表面积和丰富表面羟基的亚稳态活性氧化铝水合物晶种浆料,该晶种无需任何外加形貌调节剂或机械研磨即可获得适宜活性;其次,在种分反应中,将活性氧化铝水合物晶种浆料加入到氧化铝浓度为特定范围的铝酸钠溶液中,并控制晶种添加量以及种分反应温度,利用大量活性晶种提供的低能异相成核位点,使铝酸根离子优先在晶种表面发生异相成核与生长而非溶液中的自发均相成核,从而实现成核与生长的动力学分离,将析出的氢氧化铝颗粒粒径精确控制在亚微米级别且分布集中,得到超细氢氧化铝前驱体;最后,将超细氢氧化铝前驱体与水混合打浆得到前驱体浆料,在控制水热温度和时间条件下进行水热压煮,利用前驱体到勃姆石的拓扑转变机制使产物晶粒尺寸严格继承前驱体粒径,同时完成向纯相勃姆石的完全转化,最终获得粒度为亚微米级、无杂相、分散良好的超细勃姆石粉体,以廉价无机盐原料和温和工艺条件同时达成了低成本、高纯度、绿色环保和易于放大的目标。
Smart Images

Figure CN122586093A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of inorganic non-metallic material preparation, and in particular to a method for preparing ultrafine boehmite. Background Technology
[0002] Boehmite (γ-AlOOH) is widely used as a flame-retardant filler, lithium-ion battery separator coating, and catalyst support due to its unique microstructure and chemical stability. In lithium-ion battery separator coating applications, only boehmite with a small average particle size and concentrated distribution can form a uniform and dense coating layer, thereby effectively improving the heat resistance and safety performance of the separator. However, currently available preparation routes still face significant limitations in practical scale-up and product quality control.
[0003] While the organic aluminum alkoxide hydrolysis method produces high-purity products with regular particle sizes, it relies on expensive organoaluminum raw materials and large amounts of organic solvents, resulting in high synthesis and post-processing costs, making it difficult to adapt to large-scale production and application. In routes using inorganic aluminum salts or aluminum hydroxide as raw materials, the patent "A method for controlling the morphology of boehmite" (CN202011477897.9) adjusts the morphology of boehmite by adding magnesium chloride during the synthesis stage. However, the magnesium element leads to a decrease in purity due to entering the crystal lattice or adsorbing on the product surface. The patent "A method for controlling the morphology of high-purity flaky boehmite" (CN202110923516.3) introduces ammonium chloride and ammonium sulfate as morphology regulators. Although it can obtain flaky high-purity boehmite, the introduction of ammonium salts causes excessive ammonia nitrogen in the wastewater, increasing the environmental burden. The patent "A method for preparing boehmite" (CN202511164363.3) discloses a method for producing boehmite by mixing and grinding aluminum hydroxide, water, and a grinding aid for 0.5 to 8 hours, followed by a hydrothermal reaction. Using coarse-grained aluminum hydroxide as raw material, the raw material must be pre-ground to micron or submicron size before hydrothermal preparation of boehmite. This method is not only energy-intensive and time-consuming, but also prone to introducing foreign impurities due to wear of the grinding media, affecting the purity of the final product. Furthermore, some inorganic aluminum salt neutralization and precipitation methods require the use of surfactants or template agents to induce nucleation, making process control difficult and resulting in insufficient batch stability of the product. Summary of the Invention
[0004] This application provides a method for preparing ultrafine boehmite to solve the following technical problem: how to provide a method for preparing ultrafine boehmite that is both low-cost and environmentally friendly. This application provides a method for preparing ultrafine boehmite, the method comprising: An aluminum sulfate solution is neutralized with a sodium aluminate solution to obtain an active alumina hydrate seed slurry; wherein the solid content of the active alumina hydrate seed slurry is 2% to 6% by mass of alumina, and the final pH value of the neutralization reaction is 7 to 10. The activated alumina hydrate seed slurry is added to a sodium aluminate solution with an alumina concentration of 90 g / L to 110 g / L, and a seeding reaction is carried out under stirring to obtain a decomposed slurry; wherein, the mass of alumina contained in the activated alumina hydrate seed slurry accounts for 10% to 40% of the total mass of alumina in the sodium aluminate solution, and the temperature of the seeding reaction is 30℃ to 65℃. The decomposed slurry was subjected to solid-liquid separation and the filter cake was washed to obtain an ultrafine aluminum hydroxide precursor. The ultrafine aluminum hydroxide precursor is mixed with water and pulped to obtain a precursor slurry with a solid content of 10% to 30%. The precursor slurry was hydrothermally boiled at 170℃~220℃ for 1 hour to 4 hours to obtain ultrafine boehmite powder.
[0005] Optionally, the solid content of the activated alumina hydrate seed slurry is 2.5% to 5.5% by mass of alumina, and the endpoint pH value of the neutralization reaction is 7.5 to 9.5.
[0006] Optionally, the solid content of the activated alumina hydrate seed slurry is 3% to 5% based on the mass of alumina, and the endpoint pH value of the neutralization reaction is 8 to 9.
[0007] Optionally, the mass of alumina contained in the activated alumina hydrate seed slurry accounts for 15% to 35% of the total mass of alumina in the sodium aluminate solution.
[0008] Optionally, the mass of alumina contained in the activated alumina hydrate seed slurry accounts for 20% to 30% of the total mass of alumina in the sodium aluminate solution.
[0009] Optionally, the temperature of the seeding reaction is 40℃~55℃.
[0010] Optionally, during the hydrothermal cooking of the precursor slurry, the hydrothermal temperature is 190℃~210℃ and the hydrothermal time is 2 hours~3 hours.
[0011] Optionally, after hydrothermally cooking the precursor slurry, the process further includes: naturally cooling the hydrothermally cooked precursor slurry to room temperature, and then washing and drying the naturally cooled precursor slurry to obtain ultrafine boehmite powder.
[0012] Optionally, the particle size d50 of the ultrafine boehmite powder is 100nm~500nm.
[0013] Optionally, the ultrafine boehmite powder is pure phase γ-AlOOH.
[0014] The technical solutions provided in this application have the following advantages compared with the prior art: This application provides a method for preparing ultrafine boehmite, the method comprising: neutralizing an aluminum sulfate solution with a sodium aluminate solution to obtain an activated alumina hydrate seed slurry; wherein the solid content of the activated alumina hydrate seed slurry is 2%~6% based on the mass of alumina, and the final pH value of the neutralization reaction is 7~10; adding the activated alumina hydrate seed slurry to a sodium aluminate solution with an alumina concentration of 90g / L~110g / L to carry out a seeding reaction to obtain a decomposition slurry; wherein the activated alumina hydrate seed slurry is prepared by neutralizing an aluminum sulfate solution with a mass of 90g / L~110g / L. The mass of alumina in the aluminate hydrate seed slurry accounts for 10% to 40% of the total mass of alumina in the sodium aluminate solution, and the seeding reaction temperature is 30℃ to 65℃. The decomposed slurry is subjected to solid-liquid separation to obtain a filter cake. The filter cake is washed to obtain an ultrafine aluminum hydroxide precursor. The ultrafine aluminum hydroxide precursor is mixed with water and pulped to obtain a precursor slurry with a solid content of 10% to 30%. The precursor slurry is hydrothermally pressure cooked at 170℃ to 220℃ for 1 to 4 hours to obtain ultrafine boehmite powder. In the neutralization reaction of aluminum sulfate solution and sodium aluminate solution, by controlling the solid content of the reaction products and the final pH value of the neutralization reaction, a metastable active alumina hydrate seed slurry with high specific surface area and abundant surface hydroxyl groups is generated in situ. This seed crystal can achieve suitable activity without any external morphology modifiers or mechanical grinding. Secondly, in the seeding reaction, the active alumina hydrate seed slurry is added to a sodium aluminate solution with an alumina concentration within a specific range, and the amount of seed crystals added and the seeding reaction temperature are controlled. Utilizing the low-energy heterogeneous nucleation sites provided by a large number of active seed crystals, aluminate ions preferentially undergo heterogeneous nucleation and growth on the seed surface rather than spontaneous homogeneous nucleation in the solution. This process achieves kinetic separation of nucleation and growth, precisely controlling the particle size of the precipitated aluminum hydroxide particles to the submicron level and ensuring their concentrated distribution, thus obtaining an ultrafine aluminum hydroxide precursor. Finally, the ultrafine aluminum hydroxide precursor is mixed with water to obtain a precursor slurry, which is then subjected to hydrothermal pressure cooking under controlled hydrothermal temperature and time conditions. Utilizing the topological transformation mechanism from precursor to boehmite, the product grain size strictly inherits the precursor particle size, while simultaneously completing the complete transformation to pure-phase boehmite. Ultimately, submicron-sized, impurity-free, and well-dispersed ultrafine boehmite powder is obtained. This approach achieves the goals of low cost, high purity, environmental friendliness, and easy scale-up using inexpensive inorganic salt raw materials and mild process conditions. Attached Figure Description
[0015] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0016] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 A schematic flowchart illustrating a method for preparing ultrafine boehmite provided in this application embodiment; Figure 2 The XRD pattern of the ultrafine boehmite powder provided in Example 1 of this application; Figure 3 SEM image of the ultrafine boehmite powder provided in Example 1 of this application. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0019] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values within that range. For example, the range descriptions of "1 to 6" or "1~6" cover all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms "including" and "contains" as used herein mean "including but not limited to"; relational terms such as "first" and "second" are used only to distinguish different entities or operations and do not imply an actual order or relationship; "and / or" indicates that multiple situations can exist individually or simultaneously; expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships mentioned herein, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained through commercial purchase or prepared using existing methods.
[0020] Figure 1 This is a schematic flowchart illustrating a method for preparing ultrafine boehmite, as provided in an embodiment of this application.
[0021] Please see Figure 1 This application provides a method for preparing ultrafine boehmite, the method comprising: S1. Aluminum sulfate solution and sodium aluminate solution are neutralized to obtain activated alumina hydrate seed slurry; wherein the solid content of the activated alumina hydrate seed slurry is 2%~6% based on the mass of alumina, and the final pH value of the neutralization reaction is 7~10. S2. The activated alumina hydrate seed slurry is added to a sodium aluminate solution with an alumina concentration of 90 g / L to 110 g / L, and a seeding reaction is carried out under stirring to obtain a decomposed slurry; wherein, the mass of alumina contained in the activated alumina hydrate seed slurry accounts for 10% to 40% of the total mass of alumina in the sodium aluminate solution, and the temperature of the seeding reaction is 30℃ to 65℃. S3. The decomposed slurry is subjected to solid-liquid separation and the filter cake is washed to obtain an ultrafine aluminum hydroxide precursor. S4. The ultrafine aluminum hydroxide precursor is mixed with water and pulped to obtain a precursor slurry with a solid content of 10%~30%. S5. The precursor slurry is hydrothermally boiled at 170℃~220℃ for 1 hour to 4 hours to obtain ultrafine boehmite powder.
[0022] Aluminum sulfate solution refers to a solution of aluminum sulfate (Al2(SO4)3) dissolved in water, used as an acidic aluminum source. Sodium aluminate solution refers to a solution of sodium aluminate (NaAlO2) dissolved in water, used as an alkaline aluminum source. The neutralization reaction between aluminum sulfate solution and sodium aluminate solution yields an activated alumina hydrate seed slurry with a solid content of 2%–6% by mass of alumina. If the solid content is below 2%, the number of seeds in the activated alumina hydrate seed slurry is too small, resulting in insufficient nucleation induction during subsequent seeding reactions and leading to coarser particle size in the final ultrafine boehmite powder. If the solid content is above 6%, the slurry is too viscous, resulting in uneven seed dispersion and easy agglomeration, affecting the uniformity of subsequent seeding reactions.
[0023] After the aluminum sulfate solution and sodium aluminate solution are mixed and fully reacted, the pH value of the reaction system is measured. This pH value should fall within the range of 7 to 10. If the pH value is below 7, the system is too acidic, and the resulting precipitate is an amorphous gel with poor filtration performance and excessive activity, leading to explosive nucleation in subsequent seeding reactions and severe product aggregation. If the pH value is above 10, the system is too alkaline, and the precipitate easily transforms into highly crystalline gibbsite, reducing seed crystal activity. Controlling the endpoint pH value between 7 and 10 allows for the generation of alumina hydrate seed crystals with suitable activity. In some embodiments, the solid content of the activated alumina hydrate seed slurry is 2.5% to 5.5% by mass of alumina, and the endpoint pH value of the neutralization reaction is 7.5 to 9.5. In some embodiments, the solid content of the activated alumina hydrate seed slurry is 3% to 5% by mass of alumina, and the endpoint pH value of the neutralization reaction is 8 to 9.
[0024] Seeding reaction refers to the process of adding activated alumina hydrate seed slurry to a sodium aluminate solution, utilizing the nucleation sites provided by the seed surface to induce the decomposition of aluminate ions and their deposition on the seed to form aluminum hydroxide. Before the seeding reaction begins, the mass concentration of alumina (Al2O3) in the prepared or used sodium aluminate solution is 90 to 110 grams per liter of solution. If the concentration is below 90 g / L, the seeding reaction rate is too slow, resulting in low yield; if the concentration is above 110 g / L, the solution viscosity increases, aluminate ion diffusion is restricted, spontaneous nucleation easily occurs, leading to uneven particle size.
[0025] The meaning of the alumina content in the activated alumina hydrate seed slurry being 10% to 40% of the total alumina content in the sodium aluminate solution is: the ratio (expressed as a percentage) of the mass of alumina in the activated alumina hydrate seed slurry to the total mass of alumina in the sodium aluminate solution is 10% to 40%. If the addition amount is less than 10%, the number of seeds is insufficient, the seeding reaction is mainly spontaneous nucleation, and the product particle size is large and widely distributed; if the addition amount is more than 40%, the seed is excessive, although the product particle size is fine, the seed consumption is large, and the seeding reaction time is too short to be easily controlled. In some embodiments, the mass of alumina in the activated alumina hydrate seed slurry is 15% to 35% of the total alumina content in the sodium aluminate solution. In some embodiments, the mass of alumina in the activated alumina hydrate seed slurry is 20% to 30% of the total alumina content in the sodium aluminate solution.
[0026] During the seeding reaction, the temperature of the reaction system is maintained between 30°C and 65°C. If the temperature is below 30°C, the decomposition reaction rate is extremely slow, requiring a significantly longer seeding time, which is uneconomical industrially. If the temperature is above 65°C, the decomposition rate is too fast, resulting in uneven precipitation of aluminum hydroxide, abnormal growth of some particles, and the easy formation of Bayerite impurities. The low-temperature seeding conditions of 30°C to 65°C enable slow and uniform precipitation, thereby obtaining ultrafine aluminum hydroxide precursors with concentrated particle size. In some embodiments, the seeding reaction temperature is 40°C to 55°C. After the seeding reaction is completed, a decomposed slurry is obtained.
[0027] The decomposition slurry undergoes solid-liquid separation to separate the solid particles (i.e., precipitated aluminum hydroxide) from the liquid (mother liquor), resulting in a filter cake. The filter cake is then washed to remove soluble impurities such as sulfate and sodium ions adhering to the surface of the solid particles. This ensures high purity of the subsequently obtained ultrafine aluminum hydroxide precursor and prevents impurities from affecting the performance of the ultrafine boehmite powder. The washing endpoint is typically marked by a conductivity of less than 50 μS / cm in the filtrate after washing and a satisfactory sulfate test result.
[0028] Mixing and pulping involves thoroughly mixing, stirring, or dispersing the ultrafine aluminum hydroxide precursor with water to form a homogeneous suspension. In the precursor slurry obtained after mixing and pulping, the mass percentage of solids (i.e., the ultrafine aluminum hydroxide precursor) is between 10% and 30% of the total slurry mass. If the solid content is too low (below 10%), the unit volume yield during hydrothermal pressure cooking is low, resulting in energy waste; if the solid content is too high (above 30%), the slurry has poor fluidity, leading to uneven heat and mass transfer during hydrothermal processing, which can easily cause incomplete phase inversion or particle agglomeration.
[0029] Hydrothermal pressure cooking refers to the process of placing the precursor slurry in a sealed autoclave and heating and pressurizing it at a temperature above the boiling point of water, causing the ultrafine aluminum hydroxide precursor to undergo dehydration and phase inversion to form boehmite (γ-AlOOH). The hydrothermal temperature of 170℃~220℃ refers to controlling the heating temperature inside the autoclave during the hydrothermal pressure cooking process between 170°C and 220°C. Below 170℃, the phase inversion reaction rate is extremely slow, making it difficult to completely convert to boehmite within 1~4 hours, and the product may contain residual gibbsite or amorphous material. Above 220℃, energy consumption increases, and boehmite grains are prone to overgrowth or phase transformation to form other crystal forms.
[0030] Hydrothermal time refers to the duration of hydrothermal cooking of the precursor slurry at the specified hydrothermal temperature. A hydrothermal time of less than 1 hour results in incomplete phase transformation; a hydrothermal time exceeding 4 hours leads to grain coarsening and increased energy consumption. 1 to 4 hours is sufficient to completely convert the ultrafine aluminum hydroxide precursor into boehmite while maintaining a particle size within the range of 100 nm to 500 nm. In some embodiments, the hydrothermal cooking temperature of the precursor slurry is 190°C to 210°C, and the hydrothermal time is 2 to 3 hours.
[0031] In some embodiments, after hydrothermally cooking the precursor slurry, the process further includes: naturally cooling the hydrothermally cooked precursor slurry to room temperature, and sequentially washing and drying the naturally cooled precursor slurry to obtain ultrafine boehmite powder.
[0032] The precursor slurry after hydrothermal pressure cooking is a solid-liquid mixture, in which the solid part has been transformed from ultrafine aluminum hydroxide precursor into boehmite (γ-AlOOH), and the liquid phase consists of water and a small amount of soluble impurities.
[0033] Natural cooling involves slowly cooling the precursor slurry after hydrothermal cooking from the hydrothermal temperature (170℃~220℃) to room temperature (typically 20℃~30℃). This process does not rely on external forced cooling methods (such as ice-water baths, circulating water cooling, etc.), but only on air convection and radiation heat dissipation from the container walls, allowing the material temperature to drop naturally. After hydrothermal cooking, the precursor slurry is in a high-temperature, high-pressure state. If rapid cooling is used (such as direct discharge into atmospheric pressure cold water), the drastic temperature and pressure changes may cause stress in the boehmite lattice, or even partially transform into an amorphous phase or gibbsite. Natural cooling allows the system to return to normal pressure and temperature smoothly, ensuring the uniformity and integrity of the boehmite crystal phase. At the same time, rapid cooling can cause a sudden increase in supersaturation in the solution, which may trigger secondary nucleation or interparticle bridging and agglomeration. During natural cooling, the solute in the liquid phase gradually tends to equilibrium, making it less likely for new precipitates to form, which is beneficial for maintaining the dispersibility of ultrafine boehmite powder. Natural cooling eliminates the need to activate the autoclave's forced cooling system, preventing damage to the equipment caused by thermal stress generated by rapid cooling of high-temperature, high-pressure materials, and also reducing operational risks.
[0034] Natural cooling is usually carried out after the autoclave is sealed or gradually depressurized. The cooling time depends on the volume of the autoclave and the ambient temperature, and is generally 2 to 8 hours. The embodiments of this application do not limit the specific cooling time.
[0035] The precursor slurry, after natural cooling and hydrothermal cooking, undergoes solid-liquid separation (e.g., filtration or centrifugation) to obtain a boehmite filter cake. The boehmite filter cake is then washed with a washing solution, which can be distilled water or deionized water, at a temperature controlled between 60℃ and 90℃ to improve washing efficiency. The filtrate after the final wash is collected, and its conductivity is measured. Washing is stopped when the conductivity is <50 μS / cm and the addition of barium chloride solution to the filtrate produces no white turbidity (i.e., no sulfate ions are detected).
[0036] The washed boehmite filter cake contains a large amount of water. Drying removes the free water and yields a powdered product.
[0037] In some embodiments, the particle size d50 of the ultrafine boehmite powder is 100 nm to 500 nm.
[0038] Particle size d50 refers to the particle size value corresponding to the cumulative distribution percentage reaching 50% in the particle size distribution of ultrafine boehmite powder. d50, also known as the median particle size, represents the average level of powder particle size. A particle size d50 of 100nm to 500nm for ultrafine boehmite powder is the core technical characteristic of the preparation method in this application. Ultrafine boehmite powder with a particle size d50 in the range of 100nm to 500nm can be uniformly dispersed in aqueous or solvent-based slurries, and after being coated onto the surface of a polyolefin separator, it can form a uniform, dense, and non-porous single-layer or multi-layer coating.
[0039] In some embodiments, the ultrafine boehmite powder is pure phase γ-AlOOH.
[0040] The ultrafine boehmite powder finally obtained by the preparation method of this application has the chemical composition of γ-AlOOH (boehmite). The X-ray diffraction pattern shows that it is a single boehmite crystal phase and does not contain impurities such as gibbsite, Bayerite or α-alumina.
[0041] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national / industry standards; if there is no corresponding national / industry standard, they are performed according to general international standards, conventional conditions, or conditions recommended by the manufacturer.
[0042] Example 1 Preparation of activated alumina hydrate seed slurry via neutralization reaction: Under stirring, a 40 g / L aluminum sulfate solution was slowly added to a 40 g / L sodium aluminate solution at 45°C. The volume ratio of aluminum sulfate solution to sodium aluminate solution was 0.483:1. A white precipitate gradually formed as the aluminum sulfate solution was added. After the neutralization reaction was complete, the pH of the system was measured to be 8.8. The solid content of the slurry at this point was determined to be 4% based on the mass of alumina. Stirring was continued for 2 hours to obtain the activated alumina hydrate seed slurry.
[0043] Seeding reaction: Measure 1000 mL of sodium aluminate solution with an alumina concentration of 100 g / L, and add activated alumina hydrate seed slurry to the sodium aluminate solution. The amount added is calculated based on the mass of alumina contained in the activated alumina hydrate seed slurry being 20% of the total mass of alumina in the sodium aluminate solution. Stir the mixed system at a constant temperature of 50°C for 10 hours to carry out the seeding reaction, obtaining a decomposed slurry.
[0044] The obtained decomposed slurry was filtered (solid-liquid separation) to obtain a filter cake. The filter cake was repeatedly washed with deionized water at 80℃ until the conductivity of the filtrate dropped to 45 μS / cm, and no white turbidity was produced when barium chloride solution was added dropwise to the filtrate, confirming that sulfate ions had been washed away. After washing, an ultrafine aluminum hydroxide precursor was obtained.
[0045] The obtained ultrafine aluminum hydroxide precursor was mixed with deionized water and pulped to obtain a slurry with a solid content of 20%, thus obtaining the precursor slurry.
[0046] The obtained precursor slurry was transferred to an autoclave and hydrothermally cooked at 200°C for 2 hours. After hydrothermal cooking, the autoclave was allowed to cool naturally to room temperature, and the hydrothermally cooked precursor slurry was removed. The slurry was filtered, the solid was collected, washed with deionized water, and then dried at 110°C for 12 hours to obtain ultrafine boehmite powder.
[0047] X-ray diffraction was used to analyze the phase composition of the obtained ultrafine boehmite powder. All diffraction peaks corresponded precisely to the boehmite standard card (JCPDS No. 21-1307), and no impurity phases such as gibbsite or Bayerite were observed (see [link to X-ray diffraction analysis]). Figure 2 The morphology of the powder was observed using a scanning electron microscope (see [link]). Figure 3 The particle size of at least 200 particles was analyzed, and the particle size d50 was calculated to be 200 nm. The resulting ultrafine boehmite powder exhibited good dispersibility and no severe agglomeration.
[0048] Example 2 The difference from Example 1 is that in this example, the seeding reaction temperature is set to 40°C and the seeding reaction time is extended to 16 hours. The remaining steps are exactly the same as in Example 1.
[0049] The obtained ultrafine boehmite powder has a particle size d50 of 250 nm, and X-ray diffraction shows that it is a pure boehmite phase with good dispersibility.
[0050] Example 3 The difference from Example 1 is that in this example, the seeding reaction temperature is set to 60°C and the seeding reaction time is shortened to 3 hours. The remaining steps are exactly the same as in Example 1.
[0051] The obtained ultrafine boehmite powder had a particle size d50 of 370 nm, good dispersibility, and X-ray diffraction showed that it was a pure boehmite phase. The yield was slightly lower than that of Example 1.
[0052] Example 4 The difference from Example 1 is that in this example, the endpoint pH of the neutralization reaction is adjusted to 8.5; the hydrothermal temperature is set to 170°C; and the hydrothermal pressure cooking time is extended to 4 hours. The remaining steps are exactly the same as in Example 1.
[0053] The obtained ultrafine boehmite powder has a particle size d50 of 250 nm, good dispersibility, and X-ray diffraction shows that it is a pure boehmite phase.
[0054] Example 5 The difference from Example 1 is that in this example, the endpoint pH of the neutralization reaction is adjusted to 9.0; the hydrothermal temperature is set to 220°C; and the hydrothermal pressure cooking time is shortened to 1 hour. The remaining steps are exactly the same as in Example 1.
[0055] The obtained ultrafine boehmite powder has a particle size d50 of 370 nm, good dispersibility, and X-ray diffraction shows that it is a pure boehmite phase.
[0056] Example 6 The difference from Example 1 is that, in this example, the amount of aluminum sulfate solution added is adjusted so that the solid content of the resulting active alumina hydrate seed slurry is 2% by mass of alumina, and the pH value at the endpoint of the neutralization reaction is adjusted to 9.0. The remaining steps are exactly the same as in Example 1.
[0057] The obtained ultrafine boehmite powder has a particle size d50 of 450 nm. X-ray diffraction shows that it is a pure boehmite phase, and scanning electron microscopy shows that the particles are well dispersed and have no agglomeration.
[0058] Example 7 The difference from Example 1 is that, in this example, the amount of aluminum sulfate solution added is adjusted so that the solid content of the resulting active alumina hydrate seed slurry is 6% by mass of alumina, and the pH value at the endpoint of the neutralization reaction is adjusted to 8.5. The remaining steps are exactly the same as in Example 1.
[0059] The obtained ultrafine boehmite powder has a particle size d50 of 320 nm, and X-ray diffraction shows that it is a pure boehmite phase with good dispersibility.
[0060] Example 8 The difference from Example 1 is that in this example, the endpoint pH of the neutralization reaction is controlled at 7.0, and the solid content of the active alumina hydrate seed slurry is maintained at 4%. The remaining steps are exactly the same as in Example 1.
[0061] The particle size d50 of the obtained ultrafine boehmite powder was 380 nm, and X-ray diffraction showed that it was a pure boehmite phase, but the yield was reduced by about 15% compared with Example 1.
[0062] Example 9 The difference from Example 1 is that in this example, the endpoint pH of the neutralization reaction is controlled at 10.0, and the solid content of the active alumina hydrate seed slurry is maintained at 4%. The remaining steps are exactly the same as in Example 1.
[0063] The obtained ultrafine boehmite powder has a particle size d50 of 330 nm, good dispersibility, and X-ray diffraction shows that it is a pure boehmite phase, but the slurry filtration speed is slightly slower than that of Example 1.
[0064] Example 10 The difference from Example 1 is that in this example, the mass of alumina in the activated alumina hydrate seed slurry accounts for 10% of the total mass of alumina in the sodium aluminate solution. The seeding reaction time is extended to 15 hours. The remaining steps are exactly the same as in Example 1.
[0065] The obtained ultrafine boehmite powder has a particle size d50 of 450 nm, good dispersibility, and X-ray diffraction shows that it is a pure boehmite phase.
[0066] Example 11 The difference from Example 1 is that in this example, the mass of alumina in the activated alumina hydrate seed slurry accounts for 40% of the total mass of alumina in the sodium aluminate solution. The seeding reaction time is shortened to 5 hours. The remaining steps are exactly the same as in Example 1.
[0067] The obtained ultrafine boehmite powder has a particle size d50 of 180 nm, good dispersibility, and X-ray diffraction shows that it is a pure boehmite phase.
[0068] Example 12 The difference from Example 1 is that in this example, the seeding reaction temperature is set to 30°C and the seeding reaction time is extended to 14 hours. The remaining steps are exactly the same as in Example 1.
[0069] The obtained ultrafine boehmite powder has a particle size d50 of 495 nm, good dispersibility, and X-ray diffraction shows that it is a pure boehmite phase.
[0070] Example 13 The difference from Example 1 is that in this example, the seeding reaction temperature is set to 65°C, and the seeding reaction time is shortened to 6 hours. The remaining steps are exactly the same as in Example 1.
[0071] The obtained ultrafine boehmite powder has a particle size d50 of 470 nm, good dispersibility, and X-ray diffraction shows that it is a pure boehmite phase.
[0072] Comparative Example 1 The step of preparing the active alumina hydrate seed slurry via neutralization reaction is omitted. Commercially available aluminum hydroxide micropowder with an average particle size of 2 μm is used directly as the seed crystal. The commercially available aluminum hydroxide micropowder is added to a sodium aluminate solution with an alumina concentration of 100 g / L, at the same seed crystal addition amount (20%) as in Example 1. The remaining steps are exactly the same as in Example 1.
[0073] The seed reaction was extremely slow, and after filtration, the resulting decomposed slurry had coarse solid particles with a particle size of 1830 nm. The final ultrafine boehmite powder had an uneven particle size distribution, ranging from 200 nm to 1200 nm, and X-ray diffraction showed that it contained about 15% gibbsite impurity phase.
[0074] Comparative Example 2 The difference from Example 1 is that the endpoint pH of the neutralization reaction was controlled at 6.5, and the solid content of the activated alumina hydrate seed slurry was maintained at 4%. The remaining steps were exactly the same as in Example 1.
[0075] The filtration performance of the decomposed slurry was extremely poor, with filtration taking more than 2 hours (compared to only 20 minutes in Example 1). During the seeding reaction, the seed crystals were too active, leading to explosive nucleation. The final ultrafine boehmite powder had a particle size d50 of 780 nm and exhibited severe agglomeration and poor dispersibility.
[0076] Comparative Example 3 The difference from Example 1 is that the seeding reaction temperature is set to 75°C and the seeding reaction time is 3 hours. The remaining steps are exactly the same as in Example 1.
[0077] The rapid reaction rate resulted in uneven precipitation of aluminum hydroxide, with some particles exhibiting abnormal growth. The final ultrafine boehmite powder had a particle size (d50) of 1300 nm, indicating a relatively coarse particle size. Simultaneously, XRD analysis revealed the presence of a Bayerite impurity phase.
[0078] Comparative Example 4 After washing to obtain the ultrafine aluminum hydroxide precursor, the ultrafine aluminum hydroxide precursor was directly dried at 110°C for 12 hours without mixing, pulping, or hot pressing. The remaining steps were the same as in Example 1.
[0079] The product obtained was gibbsite (α-Al(OH)3), and the X-ray diffraction pattern showed no characteristic peaks of boehmite, so ultrafine boehmite powder could not be obtained.
[0080] Furthermore, one or more technical solutions in the embodiments of this application have at least the following technical effects or advantages: Clean and environmentally friendly, with no secondary pollution: This application does not add any environmentally unfriendly reagents such as organic solvents, ammonium salts, or magnesium chloride during the entire preparation process. The washing wastewater generated by this application is mainly a neutral aqueous solution containing small amounts of sodium salts and sulfates, which is easy to treat, has low environmental pressure, and meets increasingly stringent industrial emission requirements.
[0081] The process conditions are mild and energy consumption is low, making it suitable for industrial scale-up: This application uses inexpensive aluminum sulfate and sodium aluminate as starting materials, eliminating the need for expensive organoaluminum sources. The seeding reaction is carried out at a low temperature of 30℃~65℃, far lower than the high temperature of over 200℃ required throughout the process in traditional hydrothermal methods; the hydrothermal phase inversion temperature is only 170℃~220℃ and the holding time is as short as 1 hour~4 hours, significantly reducing overall energy consumption. Furthermore, the entire process does not involve energy-intensive mechanical grinding steps (avoiding the introduction of impurities through abrasion of the grinding media), making it simple to operate and easy to achieve continuous mass production.
[0082] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.
Claims
1. A method for preparing ultrafine boehmite, characterized in that, The method includes: An aluminum sulfate solution is neutralized with a sodium aluminate solution to obtain an active alumina hydrate seed slurry; wherein the solid content of the active alumina hydrate seed slurry is 2% to 6% by mass of alumina, and the final pH value of the neutralization reaction is 7 to 10. The activated alumina hydrate seed slurry is added to a sodium aluminate solution with an alumina concentration of 90 g / L to 110 g / L, and a seeding reaction is carried out under stirring to obtain a decomposed slurry; wherein, the mass of alumina contained in the activated alumina hydrate seed slurry accounts for 10% to 40% of the total mass of alumina in the sodium aluminate solution, and the temperature of the seeding reaction is 30℃ to 65℃. The decomposed slurry was subjected to solid-liquid separation and the filter cake was washed to obtain an ultrafine aluminum hydroxide precursor. The ultrafine aluminum hydroxide precursor is mixed with water and pulped to obtain a precursor slurry with a solid content of 10% to 30%. The precursor slurry was hydrothermally boiled at 170℃~220℃ for 1 hour to 4 hours to obtain ultrafine boehmite powder.
2. The method according to claim 1, characterized in that, The solid content of the activated alumina hydrate seed slurry is 2.5% to 5.5% by mass of alumina, and the endpoint pH value of the neutralization reaction is 7.5 to 9.
5.
3. The method according to claim 2, characterized in that, The solid content of the activated alumina hydrate seed slurry is 3% to 5% based on the mass of alumina, and the endpoint pH value of the neutralization reaction is 8 to 9.
4. The method according to claim 1, characterized in that, The mass of alumina in the activated alumina hydrate seed slurry accounts for 15% to 35% of the total mass of alumina in the sodium aluminate solution.
5. The method according to claim 4, characterized in that, The mass of alumina in the activated alumina hydrate seed slurry accounts for 20% to 30% of the total mass of alumina in the sodium aluminate solution.
6. The method according to claim 1, characterized in that, The temperature for the seed reaction is 40℃~55℃.
7. The method according to claim 1, characterized in that, During the hydrothermal cooking process of the precursor slurry, the hydrothermal temperature is 190℃~210℃ and the hydrothermal time is 2 hours~3 hours.
8. The method according to claim 1, characterized in that, After the precursor slurry is subjected to hydrothermal cooking, the process further includes: naturally cooling the hydrothermally cooked precursor slurry to room temperature, and sequentially washing and drying the naturally cooled precursor slurry to obtain ultrafine boehmite powder.
9. The method according to claim 1, characterized in that, The particle size d50 of the ultrafine boehmite powder is 100nm~500nm.
10. The method according to claim 1, characterized in that, The ultrafine boehmite powder is pure phase γ-AlOOH.
Citation Information
Patent Citations
A method for controlling the morphology of boehmite
CN112607759B
A method for controlling the morphology of high-purity platy boehmite
CN113651345B
A method for preparing boehmite
CN120793981B